Clinical, functional and radiological spinopelvic balance parameters assessment after transforaminal lumbar interbody fusion in grade 1 spondylolisthesis - Sawant, Ninad; Abraham, Mathew; George, Tobin; V., Easwer H.; Divakar, Ganesh (International Surgery Journal, 2020)
Background: The aim was to study effectiveness of TLIF procedure by assessing clinical and radiological spinal sagittal parameters pre and postoperatively. Methods: 8 patients who underwent TLIF procedure after diagnosis of spondylolisthesis studied prospectively. After recording general information, symptomatology, functional parameters were evaluated using visual analogue scale (VAS), Oswestry disability index (ODI), short form 12 (SF 12) and radiological sagittal balance parameters were assessed by calculating sagittal vertical axis (SVA), lumbar lordosis (LL), pelvic incidence (PI), pelvic tilt (PT), sacral slope (SS), preoperatively and postoperatively during follow up at 1 and 3 months. Results: We operated 4 (50%) patients at L4-L5 level of degenerative spondylolisthesis, 1 (12.5%) patient of degenerative spondylolisthesis at L5-S1 level and 3 (12.5%) patients of isthmic spondylolisthesis at L5-S1 level. All patients were grade 1 spondylolisthesis according Meyerding classification. After surgery all sagittal spinal balance parameters were not found to be statistically changed from the baseline, although there was minimum improvement. Regarding the clinical outcome measures, both VAS (<0.0001), ODI (<0.0001), and SF12 (<0.0001) improved after surgery significantly. Conclusions: In most case of grade 1 spondylolisthesis, there was only a minimal imbalance of the sagittal spinal balance parameters and so in situ fusion can be done. Even if a complete reduction of spondylolisthesis was not achieved during surgery, there was correction of a few of the parameters of spinal balance which were deranged preoperatively. Overall TLIF is very good procedure in terms of improvement in clinical and functional parameters in grade 1 spondylolisthesis.